Noninvasive optoacoustic imaging of breast tumor microvasculature in response to radiotherapy - Wu, Dan; Xu, Nan; Xie, Yonghua; Shen, Yang; Fu, Yunlu; Liu, Liang; Chi, Zihui; Lu, Runyu; Xiang, Renjie; Wen, Yanting; Yang, Jun; Jiang, Huabei (Frontiers in Physiology, 2022)
Detailed insight into the radiation-induced changes in tumor microvasculature is crucial to maximize the efficacy of radiotherapy against breast cancer. Recent advances in imaging have enabled precise targeting of solid lesions. However, intratumoral heterogeneity makes treatment planning and monitoring more challenging. Conventional imaging cannot provide high-resolution observation and longitudinal monitoring of large-scale microvascular in response to radiotherapy directly in deep tissues. Herein, we report on an emerging non-invasive imaging assessment method of morphological and functional tumor microvasculature responses with high spatio-temporal resolution by means of optoacoustic imaging (OAI). In vivo imaging of 4T1 breast tumor response to a conventional fractionated radiotherapy at varying dose (14 × 2 Gy and 3 × 8 Gy) has been performed after 2 weeks following treatment. Remarkably, optoacoustic images can generate richful contrast for the tumor microvascular architecture. Besides, the functional status of tumor microvasculature and tumor oxygenation levels were further estimated using OAI. The results revealed the differential (size-dependent) nature of vascular responses to radiation treatments at varying doses. The vessels exhibited an decrease in their density accompanied by a decline in the number of vascular segments following irradiation, compared to the control group. The measurements further revealed an increase of tumor oxygenation levels for 14 × 2 Gy and 3 × 8 Gy irradiations. Our results suggest that OAI could be used to assess the response to radiotherapy based on changes in the functional and morphological status of tumor microvasculature, which are closely linked to the intratumor microenvironment. OAI assessment of the tumor microenvironment such as oxygenation status has the potential to be applied to precise radiotherapy strategy.